Phytochemical Analysis and Flavonoid Content of Lempuyang Wangi (Zingiber aromaticum Val.) Rhizomes using Various Solvent Extractions - Berghuis, Nila Tanyela (Chimica et Natura Acta, 2026)
Lempuyang Wangi (Zingiber Aromaticum Val.) is a medicinal plant widely used in traditional medicine in Southeast Asia. This study aimed to extract and analyze the secondary metabolites from the rhizomes of Lempuyang Wangi using the maceration method with three different solvents: n-hexane, ethyl acetate, and 96% ethanol. The extraction yielded varying percentages depending on the solvent used, with the ethyl acetate extract having the highest yield at 16.26%. Phytochemical screening identified the presence of alkaloids, phenolics, and flavonoids in all extracts, with the ethanol and ethyl acetate extracts showing a broader range of compounds. The highest total flavonoid content was found in the ethanol extract, followed by ethyl acetate and n-hexane, indicating ethanol's superior ability to extract flavonoids. These findings demonstrate the influence of solvent polarity on extraction efficiency and compound diversity, highlighting ethanol as the most effective solvent for extracting flavonoids from Lempuyang Wangi. The measurement of total flavonoid content showed that the ethanol extract had the highest concentration, at 24.273 mg QE/g. These results provide a foundation for further research and potential applications in utilizing Lempuyang Wangi extracts for health benefits.